Integration of digital technologies into HR engineering: a conceptual model for cosmetic industry enterprises - BIALOSHYTSKYI , Mykhailo (Ways to Improve Construction Efficiency, 2025)
The digital transformation of the cosmetics industry is fundamentally reshaping the logic of human capital management: alongside the automation of operational processes, the need for comprehensive solutions in recruiting, developing, and retaining creative professionals is growing. The article substantiates the components of a conceptual model for integrating digital technologies into HR engineering, aimed at enhancing flexibility, innovativeness, and efficiency in personnel management within the industry. The main problem lies in the low level of implementation of AI, Big Data, cloud platforms, and integrated HRM solutions due to limited resources, lack of digital competencies, and cybersecurity risks. The methodology is based on a systemic approach, analysis of scientific sources and market leaders’ practices, comparison of organizational implementation scenarios, and assessment of expected effects and risks. A six-component model has been developed: technological (AI recruiting, ATS, Big Data forecasting, HRM integration with ERP/CRM); organizational (cloud platforms, digital workflows, remote interaction); human (LMS, e-learning, VR/AR training, gamification); analytical (HR analytics, KPI/OKR systems, turnover prediction models); communication (corporate networks, chatbots, feedback platforms); and strategic (integration of HR data into business analytics and career planning). The expected effects include reduced time-to-hire, improved selection quality, increased engagement and loyalty, while the main risks are cybersecurity threats, resistance to change, and technological dependency. A phased implementation scheme is proposed: diagnosis of digital maturity, selection of solutions (ATS/LMS/HRM/Big Data), piloting, integration with ERP/CRM, monitoring KPI, and feedback analytics. The novelty of the model lies in combining technological, organizational, and cultural-communication mechanisms with clear management metrics, forming an adaptive HR ecosystem. The practical value is manifested in reducing recruitment and training costs, accelerating vacancy closure, personalizing competency development, and strengthening the competitiveness of cosmetic enterprises in a dynamic market.